2017
DOI: 10.1097/ijg.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy or Transscleral Cyclophotocoagulation as Initial Treatment of Secondary Childhood Glaucoma in Northern Tanzania

Abstract: A high proportion of secondary childhood glaucoma in Northern Tanzania was caused by trauma and previous cataract surgery. Trabeculectomy was associated with better IOP control but also a higher complication rate. The ability to maintain visual function was comparable after both interventions. Failure was associated with a journey to the eye hospital (>100 km) possibly leading to late presentation with advanced disease and erratic follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“… Unlike GDD, it does not lead to a decreased number of glaucoma medications and it is mainly used as an adjunctive therapy (Phelan & Higginbotham 1995; Bock et al 1997; Hamard et al 2000; Neely & Plager 2001; Kirwan et al 2002; Autrata & Rehurek 2003; Carter et al 2007; Cantor et al 2018). There is a general tendency to the rise in IOP probably due to the regeneration of the CP requiring a more frequent need for retreatment (Phelan & Higginbotham 1995; Bock et al 1997; Hamard et al 2000; Neely & Plager 2001; Kirwan et al 2002; Carter et al 2007; Kraus et al 2014; Fieβ et al 2017; 2018; Glaser et al 2019), in particular in young and phakic patients (Kirwan et al 2002). The occurrence of postoperative IOP spikes in the first 3 months leading to IOP surgical management has been described in more than 20% of cases after CW‐TSCPC (Hamard et al 2000).…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“… Unlike GDD, it does not lead to a decreased number of glaucoma medications and it is mainly used as an adjunctive therapy (Phelan & Higginbotham 1995; Bock et al 1997; Hamard et al 2000; Neely & Plager 2001; Kirwan et al 2002; Autrata & Rehurek 2003; Carter et al 2007; Cantor et al 2018). There is a general tendency to the rise in IOP probably due to the regeneration of the CP requiring a more frequent need for retreatment (Phelan & Higginbotham 1995; Bock et al 1997; Hamard et al 2000; Neely & Plager 2001; Kirwan et al 2002; Carter et al 2007; Kraus et al 2014; Fieβ et al 2017; 2018; Glaser et al 2019), in particular in young and phakic patients (Kirwan et al 2002). The occurrence of postoperative IOP spikes in the first 3 months leading to IOP surgical management has been described in more than 20% of cases after CW‐TSCPC (Hamard et al 2000).…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“…(1) Combined trabeculotomy-trabeculectomy 68 (2) Mitomycin-C augmented trabeculectomy 14,73 Glaucoma drainage implantation (1) May consider smaller implant plate designs (2) Plan for possible tube repositioning or extension over the patient's lifetime 85 Cyclophotocoagulation Endoscopic cyclophotocoagulation 87 Goniotomy requires a clear cornea for proper visualization of the angle structures and targets around 120 degrees of the angle when performed in one quadrant through a single incision, as is most common in clinical practice. 47 Its advantages include a short operating time, its conjunctiva-sparing nature, potential for repeatability in another quadrant, and relatively low incidence of complications when performed by a specialist who has experience with this procedure.…”
Section: Trabeculectomymentioning
confidence: 99%
“…In addition, examining pediatric patients can prove difficult in an outpatient setting, increasing the challenge of postoperative assessments of these complications. 13,73 Jayaram et al 74 reported 78% 1-year and 67% 5-year success rate with the use of mitomycin-C (MMC)augmented trabeculectomy in pediatric patients who had failed primary trabeculotomy in a cohort comprising mainly those with PCG. Although GDIs and CPC are reserved for refractory glaucoma cases, where refractory glaucoma refers to patients that have failed prior medical or surgical therapies, GDI is being more frequently employed following failed angle procedures due to its overall better postoperative safety profile.…”
Section: Glaucoma Drainage Implants and Trabeculectomymentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, some studies report moderate efficacy even without TI. 21 Many centers in underserved areas may have to use TSCPC as a primary treatment modality 22 and may not have access to a transilluminator.…”
mentioning
confidence: 99%